Identifying an Immune-Related Gene ST8SIA1 as a Novel Target in Patients With Clear-Cell Renal Cell Carcinoma - Hu, Xu; Yang, Yanfei; Wang, Yaohui; Ren, Shangqing; Li, Xiang (Frontiers in Pharmacology, 2022)
Clear cell renal cell carcinoma (ccRCC) is one of the most common urological cancers. The tumor microenvironment exerts an important role in tumor development. The present was performed to identify novel immune-related biomarkers. The differentially expressed genes were identified using ESTIMATE algorithm base on GEO and TCGA databases. Kaplan-Meier survival curve, univariate and multivariate analyses were performed. The association between ST8SIA1 and immune system was explored. Gene set enrichment analysis (GSEA) and online databases were used for functional annotation. ST8SIA1 was identified as a potential prognostic gene. Elevated ST8SIA1 was observed in the tumor tissues compared with adjacent normal tissues and associated with higher T stage and advanced TNM stage (all P<0.05). The mRNA and protein levels of ST8SIA1 in cancer tissues and cells are also up-regulated. Kaplan-Meier survival curve, univariate and multivariate analyses showed that higher expression of ST8SIA1 was associated with worse OS (all P<0.05). ST8SIA1 expression levels were negatively correlated with tumor purity, and positively associated with infiltrated immune cells and expression of immune checkpoint genes. Function analysis also revealed that ST8SIA1 was significantly associated with immune-related pathways. In conclusion, ST8SIA1 was identified as an immune-related gene and a potential target in ccRCC patients. Further relevant studies are required to validate our findings.